UNC-10/SYD-2 links kinesin-3 to RAB-3-containing vesicles in the absence of the motor's PH domain - Odvogmed Bayansan; Prerana Bhan; Chien-Yu Chang; Syed Nooruzuha Barmaver; Che-Piao Shen; Oliver Ingvar Wagner (Neurobiology of Disease)
Kinesin-3 KIF1A (UNC-104 in C. elegans) is the major axonal transporter of synaptic vesicles and mutations in this molecular motor are linked to KIF1A-associated neurological disorders (KAND), encompassing Charcot-Marie-Tooth disease, amyotrophic lateral sclerosis and hereditary spastic paraplegia. UNC-104 binds to lipid bilayers of synaptic vesicles via its C-terminal PH (pleckstrin homology) domain. Since this interaction is relatively weak and non-specific, we hypothesize that other, more specific, interaction schemes exist. From the literature, it is evident that UNC-104 regulator SYD-2 interacts with UNC-10 and that UNC-10 itself interacts with RAB-3 bound to synaptic vesicles. RT-PCR and Western blot experiments expose genetic relationships between unc-10 and syd-2, but not between unc-10 and rab-3. Also, neither unc-10 nor rab-3 affects UNC-104 expression. However, co-immunoprecipitation and bimolecular fluorescence complementation (BiFC) assays reveal functional interactions between UNC-104, SYD-2, UNC-10 and RAB-3. Though both SNB-1 and RAB-3 are actively transported by UNC-104, motility of RAB-3 is facilitated in the presence of SYD-2 and UNC-10. Deletion of UNC-104's PH domain did not affect UNC-104/RAB-3 colocalization, but significantly affected UNC-104/SNB-1 colocalization. Similarly, motility of RAB-3-labeled vesicles is only slightly altered in nematodes carrying a point mutation in the PH domain, whereas movement of SNB-1 is significantly reduced in this mutant. Western blots from purified fractions of synaptic vesicles reveal strong reduction of UNC-104 in rab-3/unc-10 double mutants. Our findings suggest that the UNC-10/SYD-2 complex acts as a functional linker to connect UNC-104 to RAB-3-containing vesicles. Thus, this linker complex contributes to the specificity of motor/cargo interactions.